Impact of Service Quality on Inpatient Satisfaction with New Public Service Moderation at Tangguwisia Regional Hospital - Putu Karnasih; I.G.A. AG Dewi Sucitawathi P; Ian Wooton (CV. RADJA PUBLIKA, 2026)
In inpatient care, patient satisfaction is influenced by both medical and non-medical services, which can be further enhanced through the implementation of the New Public Service (NPS) paradigm. This study aimed to examine how service quality affects inpatient satisfaction at Tangguwisia Regional Hospital, with NPS serving as a moderating variable. A quantitative approach with a causal-explanatory design was employed, involving 219 inpatients at RSUD Tangguwisia. Data were collected using Likert-scale questionnaires, and the analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings revealed that service quality has a positive and significant effect on inpatient satisfaction. Additionally, NPS was found to significantly strengthen the relationship between service quality and patient satisfaction. The research model demonstrated good predictive capability with an R-square value of 0.682, indicating that service quality and NPS principles explain most of the variation in patient satisfaction. These findings underscore the importance of service quality in improving inpatient satisfaction and suggest that implementing NPS principles, such as transparency, participation, and accountability, further enhances this effect.